IRON REMOVAL OF GROUNDWATER ON THE TOWER-COLUMN WITH FOAM FILTER - , В. О., М. М. (Municipal economy of cities. Series: «Economy science», 2013)
Shows the construction process parameters and performance bashtkolon with foam filter for iron removal of water.